Pengaruh Pengaruh Kompensasi, Budaya Organisasi, dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Dinas Kepemudaan, Olahraga dan Pariwisata Kota Probolinggo - Ayu Prasanti, Dinda Puspita; Widayanto, Mutinda Teguh; Dhany, Umi Rahma (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
The research was conducted at Dinas Kepemudaan, Olahraga and Pariwisata Probolinggo City with the aim of knowing the effect of compensation, organizational culture, and work motivation partially, simultaneously and dominantly on employee performance at Dinas Kepemudaan, Olahraga and Pariwisata Probolinggo City. The type of research used is a type of quantitative research with a causal relationship. It has two variables, namely the independent and dependent ,variables.The population in this study were 30 employees of the Probolinggo City Dinas Kepemudaan, Olahraga and Pariwisata Office who already had ASN status. The sampling technique used in this research is non-probability sampling with purposive sampling technique. Sources of data used in this study come from primary and secondary data. Data were collected using questionnaires, documentation and processed by data analysis methods in the form of validity, reliability, classical assumption tests, normality tests, multiple linear regression analysis, coefficient of determination and hypothesis testing. From the partial test it shows that the compensation variable (X1) has a not effect on employee performance (Y), the Organizational culture (X2) has a significant effect on employee performance (Y) and the work motivation image variable (X3) a not effect to employee performance (Y).